Coordination of glioblastoma cell motility by PKCι - Baldwin, R M; Barrett, Gordon M; Parolin, Doris A; Gillies, Jana K; Paget, Judith A; Lavictoire, Sylvie J; Gray, Douglas A; Lorimer, Ian A (Université d'Ottawa | University of Ottawa, 2010)
Abstract Background Glioblastoma is one of the deadliest forms of cancer, in part because of its highly invasive nature. The tumor suppressor PTEN is frequently mutated in glioblastoma and is known to contribute to the invasive phenotype. However the downstream events that promote invasion are not fully understood. PTEN loss leads to activation of the atypical protein kinase C, PKCι. We have previously shown that PKCι is required for glioblastoma cell invasion, primarily by enhancing cell motility. Here we have used time-lapse videomicroscopy to more precisely define the role of PKCι in glioblastoma. Results Glioblastoma cells in which PKCι was either depleted by shRNA or inhibited pharmacologically were unable to coordinate the formation of a single leading edge lamellipod. Instead, some cells generated multiple small, short-lived protrusions while others generated a diffuse leading edge that formed around the entire circumference of the cell. Confocal microscopy showed that this behavior was associated with altered behavior of the cytoskeletal protein Lgl, which is known to be inactivated by PKCι phosphorylation. Lgl in control cells localized to the lamellipod leading edge and did not associate with its binding partner non-muscle myosin II, consistent with it being in an inactive state. In PKCι-depleted cells, Lgl was concentrated at multiple sites at the periphery of the cell and remained in association with non-muscle myosin II. Videomicroscopy also identified a novel role for PKCι in the cell cycle. Cells in which PKCι was either depleted by shRNA or inhibited pharmacologically entered mitosis normally, but showed marked delays in completing mitosis. Conclusions PKCι promotes glioblastoma motility by coordinating the formation of a single leading edge lamellipod and has a role in remodeling the cytoskeleton at the lamellipod leading edge, promoting the dissociation of Lgl from non-muscle myosin II. In addition PKCι is required for the transition of glioblastoma cells through mitosis. PKCι therefore has a role in both glioblastoma invasion and proliferation, two key aspects in the malignant nature of this disease.